Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Perilaku Seksual Remaja: Studi Literatur - Winda Dian Pratiwi; Agus Sudaryanto (Jurnal Keperawatan Malang, 2024)
Background: Teenagers are an age group that is in a stage of development both physically, mentally and psychologically which makes teenagers individuals who have a high sense of curiosity so that teenagers tend to do risky things, one of which is premarital sexual behavior. One of the factors behind teenagers becoming entangled in risky sexual behavior is a lack of knowledge among teenagers, which can be overcome by one of the interventions, namely health education. Purpose: To see the effect of reproductive health education on adolescent sexual behavior carried out by adolescents Methods: : The researcher uses a literature study method, namely by taking articles through online databases such as Science Direct, Google Scholar, and Taylor and Francis Online and selecting articles based on PRISMA so that 4 articles are used in this study with a publication time limit of 7 years starting from 2017 to 2023 Result: The results of univariate and bivariate tests from 4 articles show that there is an effect on the provision of reproductive health education on sexual behavior carried out by adolescents Implication: Reproductive health education using any method has been proven to have an effect in reducing risky sexual behavior by teenagers Keywords: Reproductive Health Education; Adolescent Sexual Behaviour